Anemia and incidence of dementia in patients with new-onset type 2 diabetes: a nationwide population-based cohort study. Issue 1 (2nd August 2020) - Choi, Jae Woo; Kim, Tae Hyun; Han, Euna
Abstract : Introduction: This study aimed to examine the association between anemia and the incidence of dementia in patients with new-onset type 2 diabetes. Research design and methods: This study used the Korean National Health Insurance Service-Health Screening Cohort and included 32 590 participants aged ≥40 years who were diagnosed with new-onset type 2 diabetes between 2004 and 2007 and followed up until 2013. Anemia was defined according to the criteria provided by the WHO, hemoglobin <120 g/L for women and <130 g/L for men, and was measured from after diagnosis date of type 2 diabetes to 2007. Dementia was defined by the Classification of Diseases 10th revision code as primary diagnosis and was measured from after hemoglobin measurement to 2013. We calculated the adjusted HR (AHR) and 95% CI to assess the risk of dementia using multivariable Cox proportional hazards regression models. Results: We identified 1682 patients who developed dementia within a 7.5-year follow-up. Among patients with type 2 diabetes, patients with anemia were associated with an increased risk of dementia than those without anemia (AHR, 1.21; 95% CI 1.06 to 1.39). Patients with mild (AHR, 1.18; 95% CI 1.03 to 1.38) and moderate (AHR, 1.39; 95% CI 1.06 to 1.83) anemia were associated with an increased risk of dementia than those without anemia among patients with type 2 diabetes. Men (AHR, 1.47; 95% CI 1.16 to 1.83) and middle-aged adults (AHR, 1.31; 95% CI 1.03 to 1.75) with anemia were associated with an increased risk of dementia than their counterparts without anemia among patients with type 2 diabetes. Conclusions: Our findings suggest that anemia is significantly associated with an increased risk of dementia among patients with newly diagnosed type 2 diabetes.